REDE POLÍTICA E INSERÇÃO INTERNACIONAL DA CADEIA PRODUTIVA DA MADEIRA EM GUARAPUAVA-PR - Santos, Patrícia dos (2015)
The present study was to analyze the political network of the productive chain of wood in Guarapuava - PR, from the international insertion (export practices). Guarapuava that in the 1940s was polo representative of wood, still remains its industrial activities wood, although less expressive. Today the search industry to leverage the international insertion of claims, from the export practices, made up of several actors with different powers and that relate from a political network. Moreover, the approach of the concept of territory allowed the study of a space that is endowed with power relations, in this case the territory of the wood. In the methodological procedures adopted formalized is an exploratorydescriptive, because it is a case study, in the wood production chain, and the world of research policy network established by the chain. For both, the research was guided by theoretical, questionnaires, using the UCINET (Software for Social Network Analysis) software and secondary data collection. It was considered, therefore, that the political network of the productive chain of wood in Guarapuava, still is submitted in a fragile, because, the relations of its actors, in many cases occur independently, since the class entities representing the industry, do not have political resources sufficient to allow actions for companies in chain.